2017
DOI: 10.1097/mat.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

Hepatogenic Differentiation of Human Induced Pluripotent Stem cells on Collagen-Coated Polyethersulfone Nanofibers

Abstract: Many scientists have been fascinated with induced pluripotent stem cells (iPSCs) for cell replacement therapies. Nanofibrous biocompatible scaffolds have been shown to foster better cell adhesion and improve stem cell differentiation. In the current study, after fabrication using electrospinning technique and surface modifications, the characteristics of polyethersulfone (PES) nanofibers were determined by scanning electron microscopy, attenuated total reflection Fourier transform infrared spectroscopy, and 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…As well as in line with enderami and mansuor in 3 D culture, these markers were significantly more expressed than cells which were induced in two dimentional. Similar to our finding, Mahmoodinia et al [38] performed differentiation of human iPSCs on IPCs on hybrid nanofibrous scaffold and they showed successful expression of protein marker C-peptide in IPS Cell-derived Insulin-Producing Islet-Like cells.…”
Section: Discussionsupporting
confidence: 91%
“…As well as in line with enderami and mansuor in 3 D culture, these markers were significantly more expressed than cells which were induced in two dimentional. Similar to our finding, Mahmoodinia et al [38] performed differentiation of human iPSCs on IPCs on hybrid nanofibrous scaffold and they showed successful expression of protein marker C-peptide in IPS Cell-derived Insulin-Producing Islet-Like cells.…”
Section: Discussionsupporting
confidence: 91%
“…But the expression level of ALB and CK‐18 in cells cultured on PLLA scaffold in her study was significantly lower than our result, in which cells differentiated on PLLA/PCL membrane, this inconsistency may be due to the type of stem cell and the nanofiber used. Additionally, Mahmoodinia Maymand et al () have demonstrated that the expression level of marker ALB in hepatocyte differentiated on PES is lower than our result that is five‐folds. These results show that hiPSCs may be better differentiated on hybrid scaffold than single PES nanofibrous membrane.…”
Section: Discussioncontrasting
confidence: 74%
“…Nanofibrous scaffolds are synthetic biocompatible scaffolds which have topographic structures that can be fabricated to mimic the structures of natural ECM (Mashhadikhan, Soleimani, Parivar, & Yaghmaei, ). Preliminary studies have used various scaffolds such as, polyethersulfone (PES; Hashemi et al, ; Kazemnejad et al, ; Mahmoodinia Maymand et al, ), poly‐ l ‐lactic acid (PLLA; Feng et al, ; Ghaedi, Soleimani, Shabani, Duan, & Lotfi, ), and PCL/collagen/PES (Mahmoodinia Maymand et al, ) for hepatocyte differentiation. However, these scaffolds have limitations, for example, Y.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun PES nanofibrous scaffold was according to a protocol modified with Shabani et al [26,27] and after plasma treatment [28], more surface modification was performed by a coating of the collagen on the surface of the fabricated PES nanofibers. Collagen solution (0.1 ng/ml, Sigma Aldrich, St. Louis, MO) was added to the nanofibers and incubated at 4 C overnight and later washed two times by PBS.…”
Section: Nanofibrous Scaffold Preparationmentioning
confidence: 99%